Empirical Study of Spatial Perception in Architectural Education: Assessing Experiential Qualities Through Physical Model Based Inquiry - Cut Sannas Saskia; Agus Budi Purnomo; Ardilla Jefri Karista; Maria Elizabeth (Ikatan Peneliti Lingkungan Binaan Indonesia, 2026)
This study explores the perception of space felt by humans through architectural models, to see the influence of architectural elements, especially lighting parameters, brightness, elevation and volumetric proportions, influencing human interpretation of the designed environment. This study was carried out by examining 51 model variations with a room area of 4x4x3.5 meters, the model variations were based on variable settings consisting of three main aspects: position of the ceiling, floor and openings; window opening size; as well as ceiling and floor heights. Based on the findings of this study, it is revealed that perceived brightness, spaciousness and comfort significantly influence spatial evaluation, especially the sense of space to improve the quality of the architectural space experience. Among all variables, comfort emerged as the most influential factor, thus strengthening its role as a core indicator of the success of spatial configuration. This study emphasizes the relevance of physical models not only as a representation tool but as an instrument for measuring the sense of space in architectural works. In architectural education, students use architectural models as the representation of design. This study uses the architectural model approach to measure human perception of space through students, but this study still has limitations compared to evaluating directly on space at the actual scale.